Moderation effect of religiosity on psychological empowerment - affective commitment relationship - Wan Yunan, Wan Rahim; Ahmad, Aminah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
Although the concept of affective commitment in the workplace has received massive attention from contemporary researchers, very little or inadequate research has been conducted from the religious and psychological empowerment perspective. This conceptual paper attempts to improve the understanding of the manner religiosity and empowerment influence employee’s commitment in the workplace. To achieve this we develop a model that includes psychological empowerment as independent variable, religiosity as a moderator and affective commitment as the dependent variable using the Social Exchange Theory (SET) as well as previous research findings. In addition, the model would extend the use of SET in understanding the role of religiosity in the psychological empowerment – commitment relationship.